Doskonalenie rachunku społeczno- ekonomicznego w gospodarce socjalistycznej - Gołębiowski, Ryszard (Wydział Prawa i Administracji UAM, 1975)
The author has proposed that the production costs should also comprise the costs of environment use.
Amelioration of National Accounting in the Socialist Economy